2021
DOI: 10.1155/2021/7564827
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Self-Reported Vision Disability among the Elderly in Malaysia: Findings from National Health and Morbidity Survey (NHMS) 2018

Abstract: Introduction. Disability has adverse effects on health, wellbeing, and life quality. Vision disorder is one of the top-ranked causes of disability in the elderly population. This study aims to determine the prevalence and factors associated with vision disability among the elderly in Malaysia. Methodology. Data collection from National Health and Morbidity Survey (NHMS) 2018 was obtained. This survey focused on elderly health by using two-stage stratified cluster sampling design. The Washington Group Extended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…The present study also revealed that the abuse prevalence was higher in older patients, which is consistent with the findings of the study by Sathya et al These authors showed that the rate of elder abuse increased with age (27). With age, the disability of the elderly exacerbates, and this factor can lead to an elevation in elder abuse (27,28).…”
Section: Discussionsupporting
confidence: 92%
“…The present study also revealed that the abuse prevalence was higher in older patients, which is consistent with the findings of the study by Sathya et al These authors showed that the rate of elder abuse increased with age (27). With age, the disability of the elderly exacerbates, and this factor can lead to an elevation in elder abuse (27,28).…”
Section: Discussionsupporting
confidence: 92%